PENGEMBANGAN MEDIA ILUSTRASI DIGITAL UNTUK MEMAHAMI LATAR TEMPAT DAN WAKTU DALAM PUISI KO-UTA (å°å”„) LITTLE SONGS OF THE GEISHA KARYA LIZA DALBY - Mulyo Saputri, Ovie Riswana (HIKARI, 2020)
-newline"> In learning languages, especially Japanese can not be separated from learning culture and literature.However, literary learning media are still lacking so researcher make research on the development ofmedia for literary learning.This research is entitled by "Development of Digital Illustration Media to Understand the Settingof Place and Time in Ko-uta Poetry? ? ? ? Little Songs Of The Geisha by Liza Dalby" with twoproblem statements in it, namely how the development process of digital illustration media to understandthe setting of place and time in ko-uta poetry. Next is how the student?s respond to digital illustrationmedia to understand the setting of place and time in ko-uta poetry.The research for digital illustration media was carried out at SMA Negeri 19 Surabaya in theJapanese specialization class XII IPS 3. In this study Sugiyono's research and development method wascarried out up to the 7th stage, namely product revision. The potential and problem stage and the datacollection stage were obtained from a pre-research questionnaire that was given to Social Sciences classXII SMA 19 Surabaya. The data used for media material was obtained from the poetry of the Little Songsof The Geisha which are grouped by four seasons. The ko-uta poem is analyzed to find the setting ofplace and time as material used to create digital illustration media. Then the product design is carried out,which is making an initial media design that will be validated at the design validation stage. After that, adesign revision was made to correct existing errors, and product trials were conducted in class XII IPS 3of SMA Negeri 19 Surabaya by filling in the student response questionnaire and the final stage of productrevision.The results of the research conducted showed that the digital illustration media got a percentage as84% of the student questionnaire responses, 84.44% of the validation of media experts, and 90% of mediamaterial experts. The calculation is done based on a Likert scale with a very strong score interpretation sothat this digital illustration media is appropriate to be used to understand the setting of place and time inthe poetry of the Little Songs of The Geisha.Things that need to be considered in research to develop Japanese literature learning media is toensure adequate facilities for the media, especially facilities in the classroom. Then it can provide quizzesand interesting games so that students do not get bored in the middle of literary learning.Keywords: Media development, Digital Illustration Media, Setting of Place and Time in ko-uta poetry.